Reconceptualizing Courtyards as Multi-Scale Socio-Spatial Systems in a Historic Coastal City - Ariestadi, Dian; Asikin, Damayanti; Baharum, Faizal (RUAS, 2026)
Accelerated urbanization and socio-spatial shifts threaten the multi-ethnic morphology of historic coastal cities in northern Java. This study examines the courtyard typology in the Old Town of Gresik, Indonesia's oldest port and Islamic center influenced by Arab, Chinese, Javanese, and colonial cultures. Utilizing a typomorphological approach with exploratory-explanatory methods, this research employs mapping, multi-scale morphological analysis (micro, meso, macro), and ethnographic observations. The findings indicate that the courtyard concept establishes a hierarchical spatial system integrating domestic, communal, and urban realms, driven by trade, industry, Islamic culture, and climate adaptation. At the microscale, residential courtyards function as gender-based domestic-economic spaces. At the meso-scale, streetscapes operate as “collective courtyards,” while at the macro-scale, the alun-alun (town square) and the Jamik Mosque precinct manifest as “urban courtyards.” This study reconceptualizes courtyards as interconnected multi-scale spatial systems, extending typomorphological research into socio-spatial dimensions for the contextual preservation of historic North Java coastal cities.